Design and Implementation of Hybrid Learning - Rahmi Juwita; Lukman Fajar Purwoko (International Journal of Educational Dynamics, 2022)
The aim of this writing is to describe the design and implementation of hybrid learning in SMAIT NFBS Bogor. This research uses descriptive qualitative method. The data is collected by observation, interview, documentation, and questionnaire. The design is focused on: 1) availability of infrastructure and equipment operational skills; 2) Student-focused learning; 3) Balanced interaction between teachers and students online and offline. The implementation of hybrid learning in general can be carried out according to the design and continuously improve the quality of better hybrid learning.